The Effect of Moringa oleifera Fruits Extract in Lowering Triglycerides Levels in Obesity - Abdul Halim Arif; Tiwuk Susantiningsih; Sri Wahyuningsih; Melly Kristanti; Fajriati Zulfa (Biology, Medicine, & Natural Product Chemistry, 2026)
Obesity is a global health problem that is often accompanied by hypertriglyceridemia as a manifestation of lipid metabolism disorders. Moringa fruit contains bioactive compounds that have the potential to be a natural hypolipidemic agent. Objective: This study aims to determine the effect of moringa fruit extract administration on triglyceride levels in obese model mice. An experimental study used 30 male Sprague Dawley mice divided into five groups: normal control, obesity negative control, positive control with vitamin C 15 mg/kgBB, moringa fruit extract treatment 500 mg/kgBB once daily, and moringa fruit extract treatment 500 mg/kgBB twice daily. Obesity was induced with a high-fat, high-protein feed for 49 days, followed by treatment for 14 days. Triglyceride levels were measured using the ELISA method and analyzed by the One-Way ANOVA test. The obese group showed the highest triglyceride levels (265.767 mg/dL) compared to the normal control (191.639 mg/dL). The administration of moringa fruit extract lowered the triglyceride level to 230,054 mg/dL for a once-daily dose and 212,463 mg/dL for a twice-daily dose. Statistical tests showed a significant difference (p<0.05) between the twice-daily treatment group and the obesity group. Moringa fruit extract was effective in lowering triglyceride levels in obese rats, with administration twice daily showing more optimal results.